Interactive course materials using multi-touch interfaces and augmented reality techniques - Tay, Guang Yuan (Nanyang Technological University, 2020)
This study explores the opportunity to incorporate UI and UX principles as well as series of Gamification of course materials to create an interactive learning option for students. The study looks at existing arguments about gamification as well as the effectiveness of various approaches to target guided learning. Existing products are also evaluated against to see how the topic of Data Structure visualization is implemented. Expanding on a previous game development “La Petite Fee Cosmo”, a 2D puzzle game that mimics the underlying concepts and flexibility of data structure by helping students learn in a more creative and innovative manner. The adoption and development of a Tutorial Stage along side UI/UX enhancements were made in an attempt to provide a better learning tool for innovative learning methods for Data Structures.